Challenges and barriers to HIV care engagement and care cascade: viewpoint - Bouabida, Khayreddine; Chaves, Breitner Gomes; Anane, Enoch (Frontiers in Reproductive Health, 2023)
Patients with human immunodeficiency virus (HIV) are subject to long-term management and a complex care process. Patients with HIV are clinically, socially, and emotionally vulnerable, face many challenges, and are often stigmatized. Healthcare providers should engage them with diligence in the HIV care cascade process. In this paper, we discuss from our viewpoint certain social and public health barriers and challenges that should be considered by healthcare providers to better engage patients in the HIV care cascade process and maximize its outcomes.